The Effect of Laughter Yoga Program to Reduce Stress and Increase Psychological Happiness among College Students - Fatima Hashem Darwesh; Moaid Ismail Jarjis (Zanco Journal of Humanity Sciences)
Current research aims to achieve research Objective and hypothesis through identify the significancy and non-significant difference between pre-test, post-test and follow-up post-test for both scales (stress, psychological happiness) before applying the laughter yoga program on (15) participants of the experimental group, and after the program applied. Laughter yoga program has been prepared by the researchers depended on literature. For the stress scale (Cohen et al; 2004-13 items), and for the psychological happiness scale (Hills & Argyle ,2002- 28 items) has been used. For sure the validity and reliability of scales were verified. Then, the two scales as pre-test were applied on the participants of the experimental group, and the program was applied, then post-test was achieved, then the data processing by using (Spss). the results showed: The laughter yoga program is effectiveness to decreases stress and increased the psychological happiness. The study has presented some recommendations and suggestions.